Yield And Quality of Grapes with Different Areas Of Nutrition of Grape Bushes - Konysbayev Lesbek Karabayevich (Genius Journals, 2021)
Experiments have been conducted to explore the influence of different areas of nutrition of grape bushes, that lead to the significant increase of the yield and quality of grapes. The highest yield of grape plantations was noted with the planting variant of 3x1 m (3333 bushes per 1 ha) - 2.3 kg/bush.
Keywords: Grape bush; planting scheme; feeding area; fruiting coefficient